A Case of Myoclonus–Dystonia Responding to Low-frequency Pallidal Stimulation. (5th May 2017) - Sarva, Harini; Miravite, Joan; Swan, Matthew C.; Deik, Andres; Raymond, Deborah; Severt, William Lawrence; Kopell, Brian H.
Background: High-frequency pallidal stimulation has been shown to improve various types of dystonia, including myoclonus-dystonia. Case Report: We report a case of epsilon sarcoglycan mutation-negative myoclonus–dystonia with response to low-frequency bilateral pallidal stimulation. Discussion: Low-frequency pallidal stimulation provides an effective means of treating various dystonias, regardless of genetic status, as in our case, as it provides increased programming options with fewer adverse effects.